Fire Blight Management: Physiological Assessment of Cultural Control By Pruning in Pear Orchards - Mendes, Rafael J. (2020)
The aim of this work was to evaluate the photosynthetic performance of Pear trees (cv. 'Rocha') infected with Erwinia amylovora, three months after suffering a pruning of infected branches (P-trees) compared with asymptomatic trees (C-trees) of the same orchard. Three months after pruning, P-trees looked healthy and were negative for the presence of E. amylovora. In September of 2018, fully expanded leaves of both P- and C- trees were sampled and analysed for photosynthetic parameters related to chlorophyll a fluorescence and gas exchange, alongside with pigments, total soluble sugars, starch, and ribulose-1,5-bisphosphate carboxylase/oxygenase (RuBisCO) contents. No significant differences were found in chlorophyll and carotenoids levels, but anthocyanins significantly decreased in P-trees. Also, despite the maximum quantum yield (Fv/Fm) significantly decreased in P-trees, the effective quantum yield of the PSII was maintained, paralleled with no changes in gas exchange parameters (PN, gs, Ci, E, iWUE, PN/gs), nor in RuBisCO relative content. Finally, the maintenance of the levels of total soluble sugars and starch also supports that the photosynthetic performance of P-trees, three months after pruning, reached values similar to those of the C-trees, contributing to the normal development and ripening of the fruit. Data support that pruning represents a reliable control measure against this quarantine pathogen. This work is the first evaluation of pruning in fire blight management regarding carbon metabolism in P. communis trees.